2023
DOI: 10.1111/php.13806
|View full text |Cite
|
Sign up to set email alerts
|

Tetraacetyl riboflavin derivative mediates caspase 3/7 activation via MAPK in A431 cells upon blue light influence

Abstract: An acetylated riboflavin derivative, 3‐methyl‐tetraacetyl riboflavin (3MeTARF), is a compound with high photostability and photophysical properties similar to riboflavin, including the ability to photogenerate singlet oxygen. In the present study, we compared the effects of irradiation on A431 cancer cells with blue LED light (438 nm) in the presence of 3MeTARF and riboflavin on MAPK phosphorylation, apoptosis, caspase 3/7 activation and PARP cleavage. We observed that photogenerated oxidative stress in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Our recent in vitro studies confirmed that 3MeTARF induces apoptosis of WM115 melanoma and A431 human epidermal cancer cells under blue light, while the percentage of necrotic cells did not exceed 6% [ 34 , 85 ].…”
Section: Apoptosis As a Mechanism Of 3metarf-induced Melanoma And Non...mentioning
confidence: 77%
See 4 more Smart Citations
“…Our recent in vitro studies confirmed that 3MeTARF induces apoptosis of WM115 melanoma and A431 human epidermal cancer cells under blue light, while the percentage of necrotic cells did not exceed 6% [ 34 , 85 ].…”
Section: Apoptosis As a Mechanism Of 3metarf-induced Melanoma And Non...mentioning
confidence: 77%
“…The antimicrobial activity of riboflavin on its own and in combination with UVA is widely described in the review by Farah et al [84]. [34,43,[84][85][86][87]].…”
Section: Riboflavin and Its Derivates In Pdt: Biological Issuesmentioning
confidence: 99%
See 3 more Smart Citations